KONSEP PENDIDIKAN ISLAM MENURUT MUHAMMAD NUQUIB AL-ATTAS - Fauzi Ananda (Proceeding International Seminar of Islamic Studies, 2023)
Syed Muhammad Naquib Al-Attas, is one of the thinkers and reformers of Islamic education with his fresh ideas. Al-Attas was not only an intellectual in terms of education and general Muslim issues, but also an expert in various fields of science. He is also considered as the initiator of the Islamization of science which influenced many other figures. He systematically formulated a strategy for the Islamization of knowledge in the form of an educational curriculum for Muslims. One of the ideas that is quite interesting is to offer the term ta`dib as the basis for the concept of Islamic education.